Application‐centric energy‐efficient Ethernet with quality of service support. Issue 15 (2nd July 2015) - Popescu, I.; Miyazaki, T.; Chino, M.; Wang, X.; Okamoto, S.; Gravey, A.; Gravey, P.; Veeraraghavan, M.; Brandt‐Pearce, M.; Yamanaka, N.
Abstract : An energy‐saving strategy for application‐centric networks is proposed. A new architecture for energy‐efficient Ethernet that meets the quality of service requirements for different classes of service is studied.